Ergonomics participatory oppurtunities for occupational health enhancement in Malaysian SMIs / Isa Halim - Halim, Isa (2006)
The thesis consists of seven chapters represents a total of two years of effort . This thesis begins with an introductory chapter about Malaysian Small and Medium Industries (SMIs) and the roles of ergonomics participatory approach to enhance occupational health in this sector. After an introductory chapter, a critical literature review on ergonomics participatory approach is provided in the second chapter. Chapter three has been devoted to the essential detail of methodology and procedures undertaken in this research . A large number of well-labelled illustrations associated with clear explanation are provided to give the necessary insight of case study in chapter four. Chapter five presents the outcomes of the research together with the effectiveness of introduced solution. The summarization and conclusion of carried out research are rendered in chapter six. Finally, chapter seven suggests a few recommendations in order to make occupational health in Malaysian SMls become more feasible. References along with published papers are provided at the end of thesis which should be useful for those interested in studying further into specific aspects . Valuable suggestions and constructive criticism from numerous parties at various institutions have led to the preparation of this thesis. I am particularly thankful to Associate Professor Ir Dr Abdul Rahman Omar for having taken the pains to review major portions of the thesis and for giving useful suggestions for improvements . I am indebted to the authorities of ExtraBuilt Sdn Bhd, Shah Alam and Universiti Teknologi MARA, Shah Alam for having allowed me to undertake this activity and provided the necessary information and facilities. I am open to criticism and would welcome any helpful suggestions for improvement in future study.